2002
DOI: 10.1128/jcm.40.5.1581-1586.2002
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Cytomegalovirus (CMV) Infection and Disease with CMV Nucleic Acid Assays

Abstract: Human cytomegalovirus (CMV) continues to be a significant cause of morbidity and mortality among transplant recipients. Molecular assays have been developed for the detection and quantification of CMV nucleic acid. In evaluating the clinical utility of these assays, correlations with clinical outcome are essential. The Amplicor CMV Monitor and NucliSens CMV pp67 tests were compared to the CMV antigenemia assay for 45 transplant recipients and 1 patient with Wegener's granulomatosis. Twenty-three patients remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 33 publications
2
32
1
1
Order By: Relevance
“…CMV QNAT is the main alternative option to antigenemia (63)(64)(65)(66)(67)(68)(69). The testing requires expensive equipment and specialized expertise.…”
Section: Diagnosismentioning
confidence: 99%
“…CMV QNAT is the main alternative option to antigenemia (63)(64)(65)(66)(67)(68)(69). The testing requires expensive equipment and specialized expertise.…”
Section: Diagnosismentioning
confidence: 99%
“…is an employee of AcroMetrix Corp. therapeutic response. [1][2][3][4][5][6][7][8][9][10][11] Therefore, accurate, sensitive, and precise diagnostic tests that can detect and quantitate CMV viral load are essential.…”
Section: Viral Load (Vl) Assessment Of Cytomegalovirus (Cmv)mentioning
confidence: 99%
“…For both tests, it is important to avoid overinterpretation of small changes in viral load, particularly near the limits of detection of the tests. However, studies have shown that both the Amplicor and the Hybrid Capture tests are useful in monitoring viral load changes in response to therapy (1,4,12).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of quantitative CMV DNA tests in managing these patient groups has been well documented (1,4,6,(12)(13)(14). In transplant recipients, CMV load is used to diagnose active CMV disease, screen patients for the use of preemptive therapy, and monitor the response to antiviral therapy (1,4,6,11). In patients infected with human immunodeficiency virus type 1, the risk of developing CMV disease has been reported to be directly related to the quantity of CMV DNA in plasma (13,14).…”
mentioning
confidence: 99%